Immunohistochemical expression of proinflammatory enzyme COX-2 and p53 in ulcerative colitis and its associated dysplasia and colorectal carcinoma. Issue 4 (December 2016) - Elmashad, Nehal Mohamed; Ziada, Dina H.; Hasby, Eiman A.; Mohamed, Abd el motaleb
Abstract: Background/aim: Ulcerative colitis (UC) patients are at increased risk for colorectal carcinoma (CRC). It is suggested that cyclooxygenase-2 (COX-2) plays a role in sporadic CRC. The p53 gene is a tumor-suppressor gene and the most frequent site of genetic alteration found in human cancer. The aim of this study was to analyze the immunoexpression of proinflammatory enzyme COX-2 and p53 in UC, UC-associated dysplasia, and CRC, in comparison with each other and with different clinical and histopathological parameters, to clarify if they have a possible role in the pathogenesis of CRC in UC patients. Materials and methods: In this cross-sectional study, 98 patients were divided into three groups: 39 patients with UC without dysplasia, 32 patients with UC with dysplasia, and 27 patients with colorectal cancer on top of UC, in addition to 10 healthy controls. All patients underwent colonoscopy, and multiple biopsies were taken for histopathological and COX-2 and p53 immunohistochemical studies. Results: There was significant difference in the expression of COX-2 and p53 in UC-related dysplasia either without or with CRC, compared with their expression in the UC group without dysplasia. Conclusion: Adding immunohistochemical analysis of COX-2 enzyme and p53 gene to routine histological assessment may improve the accuracy of early detection of dysplasia and colorectal cancer. COX-2 and p53 can be promising chemotherapeutic/chemopreventive targets in UC patients.